Modulation of multidrug resistance‐associated proteins function in erythrocytes in glycerol‐induced acute renal failure rats. (18th November 2016) - Matsushima, Aoi; Oda, Keisuke; Mori, Nobuhiro; Murakami, Teruo
Abstract: Objectives: Evaluation of the function of multidrug resistance‐associated proteins (MRPs) expressed in erythrocytes and screening of endogenous MRPs modulator(s) in glycerol‐induced acute renal failure (ARF) rats. Methods: Concentrations of 2, 4‐dinitrophenyl‐S‐glutathione (DNP‐SG), a substrate for MRPs, in erythrocytes after administration of 1‐chloro‐2, 4‐dintrobenzene (CDNB), a precursor of DNP‐SG, were determined in control and ARF rats. The screening of endogenous MRPs modulator(s) was performed using washed erythrocytes and inside‐out erythrocyte membrane vesicles (IOVs) in vitro . Key findings: Accumulation of DNP‐SG in erythrocytes was observed in ARF rats. Uraemic plasma components exhibited a greater inhibitory effect on DNP‐SG uptake by IOVs than control plasma components and increased the DNP‐SG accumulation significantly in washed erythrocytes. Several protein‐bound uraemic toxins at clinically observed concentrations and bilirubin significantly inhibited DNP‐SG uptake by IOVs. In washed erythrocytes, bilirubin (10 μm ) andl ‐kynurenine (100 μm ), a precursor of kynurenic acid being MRPs inhibitor, increased DNP‐SG accumulation significantly. Conclusions: Glycerol‐induced ARF rats contain various MRPs inhibitors in plasma, and membrane‐permeable MRP substrates/inhibitors including their precursors inhibit the MRPs function in erythrocytes cooperatively.